Temperature-dependent development and stage-specific mortality of immature Oulema duftschmidi (Redtenbacher) life stages, in comparison to O. melanopus (L.) and O. gallaeciana (Heyden) (Coleoptera Chrysomelidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
In a restricted temperature range, the development and stage-specificmortality of Oulema duftschmidi (Redtenbacher) eggs, larvae and pupae, arecompared to the responses of corresponding O. melanopus (L.) and O. gallaeciana(Heyden) life stages. The developmental rates are similar on the egg stage, whileO. duftschmidi larvae and pupae developed slower than the corresponding lifestages of the two other species. The developmental threshold of all life stages washighest for O. duftschmidi. For the three life stages of each species, a linear modelwas found satisfactory to describe the developmental rate - temperaturerelationship. In genera!, the stage-specific mortality is highest in O. duftschmidilife stages. On the larval and pupal stages, O. duftschmidi responds with increasing,and the other two species with decreasing mortality rates to a temperature increasefrom 20 to 25°C.
Keywords: Oulema duftschmidi; temperature-dependent development; stagespecific mortality